Tachyonic production of dark relics: classical lattice vs. quantum 2PI in Hartree truncation - Kimmo Kainulainen; Sami Nurmi; Olli Väisänen (Journal of High Energy Physics)
Abstract We study the out-of-equilibrium production of non-minimally coupled self-interacting scalar dark matter during reheating using classical lattice simulations. The outcomes of the classical simulations are in qualitative agreement with the previous results obtained using the quantum 2PI approach in the Hartree truncation. In particular, the novel non-linear resonance found in the 2PI Hartee study is present also in the classical lattice simulations and can dominate the final dark matter yield. For the parameters considered, the difference in final value of the scalar two-point function between the two approaches is a factor of O $$ \mathcal{O} $$ (1).